2020
DOI: 10.1007/s10488-020-01092-5
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking Patterns Among the General Population in Singapore: Results from the Singapore Mental Health Study 2016

Abstract: This study aimed to establish lifetime mental health service utilisation among the general population of Singapore. The sociodemographic correlates of those seeking help from different service provider groups and changes in lifetime mental health service utilisation between 2010 and 2016 among those with mental disorders were also explored. A population-based cross-sectional epidemiological household survey of the Singapore resident population aged 18 years and above was conducted from 2016 to 2018, using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
3
7
0
Order By: Relevance
“…Both major stakeholders acknowledged that help-seeking behavior among university students is lacking. This was supported by a recent mental health survey in Singapore, which found that more than one-third of those with mental health conditions never sought help for their mental health issues in their lives [ 5 ]. Our study, however, found a much more complex structure of support among our participants.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Both major stakeholders acknowledged that help-seeking behavior among university students is lacking. This was supported by a recent mental health survey in Singapore, which found that more than one-third of those with mental health conditions never sought help for their mental health issues in their lives [ 5 ]. Our study, however, found a much more complex structure of support among our participants.…”
Section: Discussionmentioning
confidence: 87%
“…The median age of onset of CMDs in Singapore is 22 years and most people with CMDs do not seek treatment within the first year of onset [ 4 ]. Furthermore, only 32% of those who have ever been diagnosed with a CMD have sought help from a specialized service provider [ 5 ], with a notable treatment gap identified among youth [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such discrepancy contributes to excess mortality and reduced life expectancy amongst PMDD (Parks et al 2006). Moreover, community-based primary care represented the first point of contact where persons with mental health conditions would seek help (Shafie et al 2021). Thus, existing community resources should be revised accordingly to integrate the care of both physical and psychological ailments amongst PMDD.…”
Section: Discussionmentioning
confidence: 99%
“…Version 3.0 of the Composite International Diagnostic Interview (CIDI-3.0) was initially developed for use in the World Health Organization-World Mental Health (WHO-WMH) survey and optimized for better effectiveness in community surveys [27]. CIDI-3.0 was used to assess lifetime and 12-month occurrence of DSM-IV disorders including MDD, dysthymia, generalized anxiety disorder, another anxiety disorder and/or alcohol abuse or dependence [28,29]. Prior literature has found that (1) the sensitivity of CIDI-3.0 screening was between 60.4% and 93.1%, the specificity was between 33.6% and 92.7%, the positive predictive value was between 60.1% and 95.1%, and the negative predictive value was between 68.1% and 93.7%; (2) the specificity of CIDI-3.0 diagnosis was between 97.1% and 98.9%, the sensitivity was between 33.3% and 70.3%, the positive predictive value was between 66.7% and 95.7%, and the negative predictive value was between 87.7% and 95.4%; (3) the diagnostic consistency of investigators Kappa = 0.78; (4) the test-retest reliability Kappa was between 0.737 and 1.0 [26].…”
Section: Major Depressive Disordermentioning
confidence: 99%